LF-NMR/MRI Determination of Different 6-Benzylaminopurine Concentrations and Their Effects on Soybean Moisture - Gu, Ying; Chen, Yi; Yue, Xia; Xiong, Peng; Pan, Dayu; Song, Ping; Luo, Bin (Frontiers in Plant Science, 2022)
In this study, we aimed to clarify the distribution and dynamics of water in the Xudou 20 soybean cultivar post-germination after culturing plants with various concentrations of 6-benzylaminopurine (6-BA). Low-field nuclear magnetic resonance and magnetic resonance imaging (LF-NMR/MRI), as well as principal component analysis (PCA), were used for the investigation. Results showed that low concentrations of 6-BA promoted soybean germination and high concentrations inhibited soybean germination, with 5 mg/L of 6-BA producing the most optimal conditions for growth. Moreover, the T22 determination of weakly bound water increased with increasing 6-BA concentration, and the PCA effectively distinguished soybeans cultured at different 6-BA concentrations. This study provides a method for the rapid detection of 6-BA concentration in bean sprouts. Our study provides theoretical support and solutions for industrial production guidance and bean sprout quality assessment.